Curating contemporary art in the framework of the planetary commons. Issue 2 (3rd July 2017) - Triscott, Nicola
Abstract: Within the expanded field of contemporary art, there is an increasing sense of urgency to engage with the politics of ecology in the face of accelerating environmental crises and widening social inequality. In recent years, much of contemporary art's response to socioecological issues has been framed by the concept of the Anthropocene. However, the notion of the Anthropocene has been criticised for its limited political agency and direction, indicating that there is a need for alternative interpretative frameworks. This paper proposes the notion of the planetary commons as a tactical and interpretative framework for curating art-led projects in the realm of eco- and geopolitical concerns. It discusses my curatorial interests and role in several interdisciplinary art projects that have engaged with the Polar Regions and Outer Space. It outlines artistic strategies, including critique, inquiry, representation and sociopolitical intervention, and how the projects address issues of spatial politics, environmental stewardship, and local-global governance structures. I argue that the perspective provided by this framework enables meaningful knowledge crossing different disciplines and reveals insights into the complexity of governance in the global system, highlighting the roles that art and cultural practices can play in shaping our understanding of complex societal-environmental-technological assemblages.